SOSIALISASI PENCATATAN LAPORAN KEUANGAN SEDERHANA UNTUK UMKM KERUPUK DUA RASA DI DESA SUBAN LAMPUNG SELATAN - Fitri Agustina (COMMENT: Journal of Community Empowerment, 2022)
Suban Village is located in Merbau Mataram District, South Lampung Regency, is an area that has great potential in producing food, handicraft, textile and agribusiness industries. One of the industries that is developing is the cracker industry, which is a home or family industry that makes this industry a source of family income. With the assistance activities carried out by this community service team regarding financial records, it will be able to increase understanding of simple financial records. As a result of the activities carried out, MSME actors stated that it was not difficult to keep records, it was easy to calculate sales profits properly. With an understanding of financial reports, business management will be better so that it can build a strong business, and win the competition in the long term.